A concepção da coordenação pedagógica na rede municipal de ensino : formação, o papel e saberes necessários - Konrath, Raquel Dilly (2008)
This dissertation takes as a central subject the conception of the pedagogic co-ordination in the municipal net of teaching: formation, the action and essential learnings, based on the research with the secretaries of education and with the pedagogic co-ordinators from Dois Irmãos, Ivoti, Morro Reuter, Lindolfo Collor and Presidente Lucena.To understand and conceive the pedagogic co-ordination space in the present time, the research brings in the first chapter the beginning of the school supervision, its historical evolution in the education context and it analyses the models of its agreement in the cities investigated. The second chapter describes and analyses the actions of the pedagogic co-ordination in the present time, its function, its new challenges and needs, through different theoretician s views, from the secretaries of education and pedagogic co-ordinators. The last chapter presents the pedagogic co-ordination also in the theological dimension, assuming a position and a loving and careful attitude with others, committed to the personnel and professional development from the general school.